Performance Evaluation of Bioretention Systems in Selected Residential Area - Farah Syaza Mahmod,; Norashikin Ahmad Kamal,; Jing Lin Ng,; Sangmin Shin, (International Journal of Integrated Engineering, 2025)
Managing stormwater runoff in urban areas is increasingly challenging, leading to strain on drainage systems, flooding, and environmental degradation. This research examines the effectiveness of bioretention systems in mitigating stormwater runoff in the residential area of Eco Majestic, Semenyih. The EPA SWMM 5.1 model was used to simulate stormwater scenarios both with and without bioretention systems to assess their impact. The findings show that bioretention systems reduce runoff volume by 92.63%, which significantly lowers surface runoff and lowers the risk of floods, while also increasing infiltration rates to ease the strain on conventional drainage infrastructure. Furthermore, a cost-benefit analysis indicates savings from reduced flood damage and other environmental benefits, proving the systems' economic viability. Beyond its effects on hydrology, bioretention systems improve community well-being, biodiversity and urban aesthetics, all of which support sustainable urban development. This study emphasizes the significance to incorporate bioretention systems into urban development to manage stormwater issues and build environmental resilience. Future research should study field monitoring, long term performance in variety of climates and wider ecological and socioeconomic benefits to enhance the use of bioretention systems in urban areas.